Synthesis of deca-dodecasil 3 rhombohedral (dd3r) membranes via secondary hydrothermal growth method and their gas permeation performance in co2 and ch4 - Mubashir, M. (Asian Research Publishing Network, 2016)
In the present work, DD3R zeolite membranes were synthesized on a-alumina support using dip-coating and vacuum-assisted seeding secondary growth methods, respectively. DD3R seeds were synthesized using two different routes; (i) ultrasonic irradiation pretreatment coupled with hydrothermal heating for 1 day at 160 °C and (ii) hydrothermal heating for 25 days at 160 °C without ultrasonic irradiation pretreatment. Subsequently, the DD3R membranes were grown on the seeded support in 2 days at 160 °C via hydrothermal heating method. The resultant membranes were characterized using X-ray diffraction (XRD) and field emission scanning electron microscope (FESEM). The XRD and FESEM results showed that all membranes demonstrated DD3R topology. The resultant membranes were subjected to gas permeation study and CO2/CH4 selectivity of 5.22 was obtained for the DD3R membrane synthesized via vacuum seeding method using DD3R seeds synthesized in 1 day.